FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - ELISABETH TRI ARYANTI ISTIMAWANI (E-Jurnal Akuntansi TSM, 2021)
The objective of this research is to test and analyze the variables that influence the firm value of manufacturing companies that listed in Indonesia Stock Exchange. Leverage, Liquidity, Profitability, Size of Firm, Investment Opportunity Set, Activity, Dividend Policy, Audit Committee, and Company Growth are the independent variables of this research. The sample of this research consists of 43 manufacturing companies listed in Indonesia Stock Exchange during 2014 to 2016 that has been selected using purposive sampling method. Multiple regression was used as statistical test method. The results of this research revealed that leverage, profitability, investment opportunity set, dividend policy and company growth influence firm’s value and other independent variables (liquidity, size of firm, activity, and audit committee) do not have any influence toward firm’s value.